2003
DOI: 10.1016/s0014-5793(03)00872-x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Bfl‐1, an anti‐apoptotic Bcl‐2 family protein, to a potent pro‐apoptotic protein by fusion with green fluorescent protein (GFP)

Abstract: Human B£-1 is an anti-apoptotic Bcl-2 family member. Here, we found that B£-1 was converted into a potent death-promoting protein by green £uorescent protein (GFP) fusion with its N-terminus. The transient expression of GFP-B£-1 induced cytochrome c release and triggered apoptosis in 293T cells, which depended on the mitochondrial localization of GFP-B£-1. Apoptosis induced by GFP-B£-1 was signi¢cantly blocked by the pan-caspase inhibitor carbobenzoxy-Val-Ala-Asp-£uoro-methyl ketone, but was not blocked by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…41 These observations with Bfl-1 agree with the capacity of other Bcl-2 family proteins like Bcl-2 and Bcl-xL to either suppress cell death (fully or partially) or promote apoptosis depending on the stimulus and/or the cell type. 9,10,31 Contrary to a recent report indicating that GFP-Bfl-1 is proapoptotic in transiently transfected 293T cells in the absence of a death-inducing signal, 42 we found no evidence that GFP-Bfl-1 is by itself proapoptotic, as FL5.12 cells stably expressing GFP-Bfl-1 were viable and proliferated normally. Moreover, GFP-Bfl-1 showed no toxicity when transiently expressed in other cell lines such as MCF-7 or HeLa cells (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…41 These observations with Bfl-1 agree with the capacity of other Bcl-2 family proteins like Bcl-2 and Bcl-xL to either suppress cell death (fully or partially) or promote apoptosis depending on the stimulus and/or the cell type. 9,10,31 Contrary to a recent report indicating that GFP-Bfl-1 is proapoptotic in transiently transfected 293T cells in the absence of a death-inducing signal, 42 we found no evidence that GFP-Bfl-1 is by itself proapoptotic, as FL5.12 cells stably expressing GFP-Bfl-1 were viable and proliferated normally. Moreover, GFP-Bfl-1 showed no toxicity when transiently expressed in other cell lines such as MCF-7 or HeLa cells (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have demonstrated a bifunctional property of Bfl1, with the full-length protein containing the recognized anti-apoptotic activity and the N-terminus deletion mutants displaying potent pro-apoptotic activities (Ko et al, 2003a;Yang et al, 2005). A recent study by Kucharczak et al (Kucharczak et al, 2005) showed that TNF␣ receptor activation results in in-vivo proteolysis of Bfl1 by the proteosome and calpain-like protease, thus converting Bfl1 into a pro-apoptotic molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The ATAP sequence has been implicated in targeting of Bfl1 to the mitochondrial membrane, because deletion of 17 amino acids at the C-terminus caused mistargeting of Bfl1 from the mitochondria (Ko et al, 2003a). Moreover, Bfl1s, an alternative splice variant of Bfl1 with a different C-terminal sequence, is found to localize to the nucleus (Ko et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In A375 cells, even the presence of the bulky YFP tag did not disrupt the ability of the protein to associate with the mitochondria. There have been suggestions that internal sequences in the protein may also have some responsibility for the mitochondrial localisation of Bfl-1 406,489 .…”
Section: Chapter 5 Conclusionmentioning
confidence: 99%